2021
DOI: 10.3390/ijms22084257
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Pharmacokinetic Properties of Potential Anticancer Agents via Their Chromatographic Behavior on Different Reversed Phase Materials

Abstract: The Quantitative Structure-Activity Relationship (QSAR) methodology was used to predict biological properties, i.e., the blood–brain distribution (log BB), fraction unbounded in the brain (fu,brain), water-skin permeation (log Kp), binding to human plasma proteins (log Ka,HSA), and intestinal permeability (Caco-2), for three classes of fused azaisocytosine-containing congeners that were considered and tested as promising drug candidates. The compounds were characterized by lipophilic, structural, and electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…In general, the higher the drug score, the higher the probability that the compound will be a drug in the future [28]. All the investigated isopropylated congeners (I-VI) revealed favorable physico-chemical and pharmacokinetic properties and they were devoid of undesired side effects, such as mutagenicity, tumorigenicity, irritating and reproductive effects, as previously reported [2]. It was found that a drug score for compound VI was almost the same as that of pemetrexed.…”
Section: Predicting Molecular Targets For the Isopropylated Fused Aza...supporting
confidence: 62%
See 2 more Smart Citations
“…In general, the higher the drug score, the higher the probability that the compound will be a drug in the future [28]. All the investigated isopropylated congeners (I-VI) revealed favorable physico-chemical and pharmacokinetic properties and they were devoid of undesired side effects, such as mutagenicity, tumorigenicity, irritating and reproductive effects, as previously reported [2]. It was found that a drug score for compound VI was almost the same as that of pemetrexed.…”
Section: Predicting Molecular Targets For the Isopropylated Fused Aza...supporting
confidence: 62%
“…Due to the remarkable in vitro antiproliferative effect against human tumors of the breast, cervix and lung-even stronger than that of an anticancer agent pemetrexed-and a lower toxicity to normal cells, the title compounds are of particular pharmacological importance. In addition, most of these isopropylated congeners show the protective effect on oxidatively-stressed erythrocytes, better or comparable to that of ascorbic acid and Trolox, and they are characterized by lipophilicity indices ensuring the optimal absorption and effective permeability in body compartments [1,2]. It is hoped that the most selective molecules of this class will find application in cancer chemotherapy in the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other separation techniques, micellar liquid chromatography (MLC) or micellar electrokinetic chromatography (MEEKC), respectively, in which the mobile phase comprises surfactants that allow better mapping of penetration of molecules through biomembranes can be also be used for lipophilicity determination [ 7 ]. The literature review shows that numerous publications have dealt with the subject of determining the lipophilicity of various bioactive compounds using chromatographic methods [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer active annelated asymmetrical triazines ( 1 – 5 , Figure 1 ), that have been synthesized in our laboratory, belong to antimetabolite-type molecules that may be irreversible inactivators of specific enzymes [ 1 ]. The molecular structures of these innovative heterocycles have previously been established, whereas their experimental lipophilicities (derived from the retention behavior in reversed-phase high-performance liquid chromatography on different columns, including those imitating biosystems), structural and electronic descriptors have been correlated strongly with important pharmacokinetic descriptors, resulting in highly predictive QSAR relationships suggesting their high bioavailability [ 1 , 2 ]. A three-dimensional (3D) structure of compound 2 has recently been established by X-ray crystallography.…”
Section: Introductionmentioning
confidence: 99%